A Backwards-step for Gillick: Trans Children's Inability to Consent to Treatment for Gender Dysphoria—Quincy Bell & Mrs A v The Tavistock and Portman NHS Foundation Trust and Ors [2020] EWHC 3274 (Admin). (2nd July 2021) - Moreton, Kirsty L.
Abstract: The case of Quincy Bell & Mrs A v The Tavistock and Portman NHS Foundation Trust and Ors is a judicial review into the treatment practices of the Gender Identity Development Service (GIDS) run by Tavistock and Portman NHS Foundation Trust (Tavistock). The Divisional Court considered whether children and young people with Gender Dysphoria (GD) can ever be Gillick competent to consent to treatment with Puberty Blockers (PBs), and if so whether GIDS provided sufficient information to support an informed consent. This commentary examines the six key areas of the judgment: the nature of GD and its treatment with PBs; the categorisation of PBs as experimental treatment; the high bar set to achieve Gillick competence; the convergence of information provision and competence; the role of parental consent; and finally the protective jurisdiction of the court. The conclusion of the court that transgender children aged under 16 years will find 'enormous difficulties' in reaching the Gillick threshold to be able to consent to PBs, and that even 16- to 17-year olds would benefit from a 'best interests determination' from the court, signals judicial thinking which is markedly protectionist. Considering the broad contemporary stance in healthcare of facilitating competence, valuing patient participation, and respecting rights, I argue that this judgment is out of step. It has implications not only for transgender children, but it may also be a worrying signal of a greater general retreat from Gillick and a corresponding advance in emphasis on judicially determined best interests.